2022
DOI: 10.1038/s41598-022-13396-7
|View full text |Cite
|
Sign up to set email alerts
|

Differing coronavirus genres alter shared host signaling pathways upon viral infection

Abstract: Coronaviruses are important viral pathogens across a range of animal species including humans. They have a high potential for cross-species transmission as evidenced by the emergence of COVID-19 and may be the origin of future pandemics. There is therefore an urgent need to study coronaviruses in depth and to identify new therapeutic targets. This study shows that distant coronaviruses such as Alpha-, Beta-, and Deltacoronaviruses can share common host immune associated pathways and genes. Differentially expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Molecular and cellular immune features of 31 patients aged > 70 years with severe COVID-19 pneumonia have suggested that inflammation, coupled with the inability to have a proper anti-viral response, could aggravate disease severity and the worst clinical outcome [ 9 ]. Comparative host transcriptome analysis across distant coronavirus genres showed 23 pathways and 21 Differentially expressed genes (DEGs) across ten immune response-associated pathways were shared by these viruses, and these DEGs could be utilized as specific targets for novel coronavirus treatments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular and cellular immune features of 31 patients aged > 70 years with severe COVID-19 pneumonia have suggested that inflammation, coupled with the inability to have a proper anti-viral response, could aggravate disease severity and the worst clinical outcome [ 9 ]. Comparative host transcriptome analysis across distant coronavirus genres showed 23 pathways and 21 Differentially expressed genes (DEGs) across ten immune response-associated pathways were shared by these viruses, and these DEGs could be utilized as specific targets for novel coronavirus treatments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%